Penggunaan Media Loose Part dalam Mengembangkan Kreativitas Anak Usia Dini di PAUD Tunas Harapan - Mita Oktavia Lestari; Abdul Karim Halim (Universitas Negeri Padang, 2022)
Increasing creativity in early childhood can be done by using media in the learning process. The media used can be of various types, one of which is loose part media. This study aims to develop and improve the creativity of early childhood children in PAUD Tunas Harapan in the learning process through the use of loose part media. This research is an action research. The subjects in this study were early childhood group B (5-6 years) totaling 10 people. Data collection methods used are observation and documentation. In this study, teachers and researchers collaborate in the learning process by using loose part media. The results of this study, seen from before the action was given the percentage of children's creativity was still very low, but then in cycle 1 the percentage increased to 30% for the sufficient category and 70% for the less category. In the second cycle, it increased again to 80% for the very good category and 10% for the sufficient category, and another 10% for the less category. Thus it can be concluded that research with the use of Loose Part media can develop and increase the creativity of early childhood in PAUD Tunas Harapan.